THE ROLE OF SUBSURFACE FLOW DYNAMIC ON SPATIAL AND TEMPORAL VARIATION OF WATER CHEMISTRY IN A HEADWATER CATCHMENT - Tanaka, Tadashi (Indonesian Agency for Agricultural Research and Development, 2007)
Variation of water chemistry does not merely occur due to in situ chemical process, but also transport process. The study was carried out to address the role of subsurface flow dynamic on spatial and temporal variation of water chemistry in a headwater catchment. Hydrometric and hydrochemistry measurements were done in transect with nested piezometers, tensiometers, and suction samplers at different depths across hillslope and riparian zone in a 5.2 ha first-order drainage of the Kawakami experimental basin, Nagano, Central Japan from August 2000 to August 2001. Spatial variation of solute concentration was defined by the standard deviation and coefficient of variation of the seasonal observed concentrations. Autocorrelation analysis was performed to define temporal variation of solute concentration. The results showed that spatial variation of water chemistry was mainly influenced by the variation of subsurface flow through the hillslope and riparian zone. Solute concentration in the deep riparian groundwater was almost three times higher than that in the hillslope segment. A prominent downward flow in deep riparian groundwater zone provided transport of solutes to the deeper layer. Time series analysis showed that in the deep riparian groundwater, Ca2+, Mg2+, SO42- and HCO3- concentrations underwent a random process, Na+ concentration of a random process superimposed by a trend process, and SiO2 of a random process superimposed by a periodic process. Near the riparian surface, SO42- concentration was composed of a random process superimposed by a periodic process, whereas other solutes were mainly in a random process. In the hillslope soil water, there was no trend observed for the Na+ concentration, but there were for Ca2+ and Mg2+. The magnitude and direction of subsurface flow across hillslope and riparian zone created transport and deposition processes that changed solute concentration spatially and temporally.